Pulmonary Hypertension Associated with Stenosis of the Right Pulmonary Artery Branch in a Dog - Takuya MATSUKAWA; Nagi TOMITA; Takehito MORITA; Yoshiaki HIKASA (Acta Veterinaria Eurasia)
A 10-year-old male miniature dachshund dog was referred to our hospi tal for cough and dyspnea. Two-dimensional echocardiography revealed pulmonary hypertension with an echo-free circle structure adjacent to the dorsal side of the left atrium. The estimated systolic and mean pul monary arterial pressures were 50.4 and 36 mm Hg, respectively. The right pulmonary artery distensibility index, right ventricular fractional area per cent change, and tricuspid annular plane systolic excursion were low, sug gesting pulmonary hypertension. Treatment with furosemide, isosorbide dinitrate, beraprost sodium, and alacepril was initiated. However, the dog died 43 days later. Pathological examinations revealed right pulmonary artery stenosis and left atrial compression due to right pulmonary artery expansion. The right ventricular hypertrophy and dilation, narrowing of the left atrium, left ventricular cavity and aorta, pulmonary congestion, and edema were also observed. This was an unusual canine case of pulmo nary hypertension associated with stenosis of the right pulmonary artery branch combined with compression of the left atrium and pulmonary edema.